Management - Daft, Richard L. (Cengage Learning, 2016)
This text addresses emerging themes and the issues most important for meeting today's management demands and challenges. A blend of proven management techniques and new competencies demonstrates how to harness creativity and lead change as students learn to put theory into practice. D.A.F.T. defines Management with the best in new and proven management competencies.